Improving Students’ Reading Comprehension of Hortatory Exposition Text by Using Graphic Organizers at Grade XI Social Science of SMA Kalam Kudus Pekanbaru - Djoni Djoni; Yeni Afriyeni (Universitas Lancang Kuning, 2018)
Based on a preliminary study, the researcher found that the students at grade XISocial Science of SMA Kalam Kudus Pekanbaru had problems in comprehending hortatoryexposition texts. They were difficult to understand contents and to identify generic structureof the texts. Besides, the teacher had used some strategies in teaching readingcomprehension, but they were still not effective. In this case, the researcher decided to solvethese problems in reading by conducting a classroom action research by applying GraphicOrganizer. The purposes of this research were to find out whether Graphic Organizer canimprove students’ reading comprehension of hortatory exposition texts and the factors thatinfluence the changes of students reading comprehension of hortatory exposition texts. Thisclassroom action research was done in two cycles with four meetings in each cycle; threemeetings for teaching reading comprehension of hortatory exposition texts by applyingGraphic Organizer and one meeting for the test. The research was conducted from August02, 2017 until August 25, 2017. In collecting the data, researcher used readingcomprehension tests, observation sheets, field notes, and interview. Then, the data wereanalyzed in quantitative and qualitative. The research findings showed that there was animprovement of students’ score in reading comprehension of hortatory exposition texts testsafter applying Graphic Organizer. The average score of students in cycle 1 was 65 and cycle2 was 70. Then, the factors that influence the improvement of students’ readingcomprehension of hortatory exposition texts were students’ activeness, teaching material,and teachers’ role. In conclusion, the implementation of Graphic Organizer could improvestudents’ reading comprehension of hortatory exposition texts at grade XI Social Science ofSMA Kalam Kudus Pekanbaru.